PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SEJARAH SISWA KELAS XII IPS 1 MELALUI MODEL PEMBELAJARAN SOSIODRAMA DI SMAN 13 PADANG - Erma, Erma (TINGKAP, 2014)
The objectives of this study were (1) to explain the efforts to enhance student learning activities and to improve student learning outcomes in history subject matter at grade XII IPS 1 Semester 1 SMA Negeri 13 Padang 2013/2014. This study was conducted through a class action research for 3.5 months in the first semester. The study started from July to the middle of October 2013. The results of this study indicated that (1) Sociodrama learning models can improve students' learning activities on the history subject matter regarding proclamation of Indonesian independence; (2) the use of Sociodrama learning model can improve student learning outcomes. Key Words: Student learning activity, learning outcomes, Sosiodrama learning model.